Penerapan Model Inkuiri Terbimbing sebagai Solusi Keaktifan Peserta Didik di SMP N 01 Tiumang Dharmasraya - Nurkhasanah, Ani Fitria; Sabri, Ahmad; Nelwati, Sasmi (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
From this research, the objectives are: 1) Describe the problems in the PAI learning process at SMP N 1 Tiumang. 2) Analyze the application of the guided inquiry model as a solution to PAI and BP learning problems at SMP N 1 Tiumang. 3) Analyze the impact of using the guided inquiry model on student activity. This research method used is a qualitative descriptive approach. Then techniques for collecting data include interviews with teachers in the PAI and BP study fields, observations at school and data obtained from various kinds of literature such as books, journals and other related sources. The results of the research show that: 1) In the learning process in the classroom the teacher is not clear about what type of learning model to use in the classroom. Learning only runs conventionally where the teacher explains the material/information in the textbook. Then the students sat down and most of them did not pay attention to the material read by the teacher. 2) The application of the guided inquiry model in the classroom is divided into 3 activities, namely the opening, core and final activities, namely the closing. In the core activity, students are divided into several groups to work on and discuss assignments that have been given by the teacher previously. 3) The impact of using this guided inquiry learning model can increase the activity of most students in class.